(untitled) (The Planet, 2023)
Introduction: Hepatic encephalopathy (HE) is a frequent complication of cirrhosis and a major public health problem. It is assumed that approximately 60-80% of patients with liver cirrhosis develop hepatic encephalopathy. The study aimed to see the prognosis of hepatic encephalopathy on discharge in a tertiary-level hospital. Methods: This prospective observational study was conducted at the Department of Medicine in Combined Military Hospital (CMH), Dhaka, Bangladesh for 6 months. A total of 50 subjects were included in this study. Result:In this study, nearly three- a fifth (58%) of the patients exhibited HBsAg, 20% had Anti HCV antibody, 6% Anti-HBc, and 14% had Non-HBV. Repeated measure ANOVA analysis revealed that the improvement of the patients in terms of these variables was highly significant (p<0.001). USG examination at baseline showed that 10% of the patients had hepatomegaly, 82% splenomegaly and 72% had ascites which reduced to 8%, 78%, and 68% respectively on 3rd day of admission and 6%, 78%, and 66% on the day of discharge. But at discharge, only 2% of the patients were classified as WHC grade-2, 10% as comatose Conclusion: The majority of the HE of moderate to severe grade in the present study came down to grade 0-1 or to unimpaired state which denotes a good prognosis. The diagnosis and grading of the severity of HE using West Haven Criteria (WHC) is of utmost importance in deciding the treatment options for a favorable outcome.